Exploiting the Cognitive and Social Benefits of Physically Large Displays - Tan, Desney ((2003) PhD Dissertation Proposal, Carnegie Mellon University, School of Computer Science, 2003)
Information elicits fundamentally different cognitive and social reactions when presented on large wall-sized displays as compared to smaller displays, even at identical visual angles. These reactions can be quantified and understood in controlled experiments and can be exploited to design display systems that make users more productive than they were on traditional systems.